Retrofitting Sambungan Kolom-Balok Beton Bertulang Ekspansi Planar Segitiga dengan Variasi Ukuran - Sigit Hernowo; Ade Lisantono (Forum Teknik, 2016)
Highly seismic activities in Indonesia, that is followed by a lot of high magnitude earthquakes, make awareness of the people to anticipate the damage that caused by this disaster. The Codes of earthquake have changed and are accompanied by the change of seismic region. There must be some efforts to improve the existing building structure. One of the efforts is retrofitting the beam-column joint which is the weakest element of structure in the building when subjected to earthquake loading. Four beam-column joint reinforced concrete specimens, namely SJC, SJ-01, SJ-02, and SJ-03, made of normal concrete and plain reinforcement were tested in this experimental program. Beam with 150 mm width, 250 mm high, and 1500 length be jointed with column that has section area of 250 mm x 250 mm, and 1750 mm length. The specimens of SJ-01, SJ-02 and SJ-03 were retrofitted by triangular voute in lower side of the beam in the beam column joint region with 125 mm, 187.5 mm, and 250 mm side length, respectively. All specimens are tested with cyclic loading using hydraulic actuator. The results show that the increasing strength of specimen SJ-01 and SJ-03 compare to the reference specimen were 12.74% and 10.29%, respectively. While the strength of specimen SJ-02 a little bit decreasescompare to the reference specimen.Keywords: beam-column joint, reinforced concrete, retrofitting, voute, cyclic loading.